(untitled) (Itinera, 2019)
Using the interruption of menstruations in the mother and still absent in the daughter as physical evidence of the broken relationship between the two women protagonists of Terremoto con madre e figlia, my reading of the play reflects on the economy of such relationship. The mother historicizes the years of feminist and political commitment and her dedication to teaching through the presence of her daughter who completely refuses her mother’s teachings. Yet, the presence of the daughter serves as an alibi – from another dimension – for the author to autobiographically reflect on the horizon of the most important events of her existence. Relational contingency allows the mother to build her personal testimony of the Utopia of the Sixty-eight.